Electrocatalysis of oxygen reduction reaction on shape-controlled pt and pd nanoparticles-importance of surface cleanliness and reconstruction - Devivaraprasad, Ruttala; Nalajala, Naresh; Bera, Bapi; Neergat, Manoj (Frontiers in Chemistry, 2019)
Shape-controlled precious metal nanoparticles have attracted significant research interest in the recent past due to their fundamental and scientific importance. Because of their crystallographic-orientation-dependent properties, these metal nanoparticles have tremendous implications in electrocatalysis. This review aims to discuss the strategies for synthesis of shape-controlled platinum (Pt) and palladium (Pd) nanoparticles and procedures for the surfactant removal, without compromising their surface structural integrity. In particular, the electrocatalysis of oxygen reduction reaction (ORR) on shape-controlled nanoparticles (Pt and Pd) is discussed and the results are analyzed in the context of that reported with single crystal electrodes. Accepted theories on the stability of precious metal nanoparticle surfaces under electrochemical conditions are revisited. Dissolution, reconstruction, and comprehensive views on the factors that contribute to the loss of electrochemically active surface area (ESA) of nanoparticles leading to an inevitable decrease in ORR activity are presented. The contribution of adsorbed electrolyte anions, in-situ generated adsorbates and contaminants toward the ESA reduction are also discussed. Methods for the revival of activity of surfaces contaminated with adsorbed impurities without perturbing the surface structure and its implications to electrocatalysis are reviewed.
Keywords: Adsorption; Dissolution; oxygen reduction reaction; Palladium; platinum; reconstruction; shape-control; surface cleaning

Polyaryletherketone in energy conversion and storage devices - a highly tailorable material with versatile properties - Feroze Gooty Saleha, Wasim; Nalajala, Naresh; Neergat, Manoj (Polymer International, 2021)
Polymers have been a highly useful class of material for the last few decades owing to their ease of bulk production and fabrication. With the myriad of applications in day to day life, they have also found an important role in energy conversion and storage devices, not just as a housing material of the device but with an important role in the energy conversion process. Among the several polymers used in this area, polyaryletherketones (PAEKs) are one of the most versatile materials owing to their easy tailorability. The ether and ketone groups can be introduced in the main polymer chain in several ways to achieve the desired material properties. The main role of a polymer in an energy conversion device is that of a barrier to avoid the mixing of reactants and to selectively transport ions from one electrode to the other to maintain charge neutrality. The polymer membrane finds application in various electrochemical energy conversion devices such as fuel cells, lithium ion batteries, redox flow batteries, supercapacitors etc. The main focus of this work is to briefly review the extent of development in the PAEKs in various energy conversion and storage devices. (c) 2021 Society of Industrial Chemistry.
Keywords: electrolyte membrane; energy conversion and storage; fuel cells; lithium ion batteries; redox flow batteries; separator